2016
DOI: 10.1038/nature17038
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic colonization by circulating tumour cells

Abstract: Metastasis is the main cause of death from cancer. To colonize distant organs, circulating cancer cells must overcome many obstacles through mechanisms that we are starting to understand. Infiltrating distant tissue, evading immune defences, adapting to supportive niches, surviving as latent tumour-initiating seeds, and eventually breaking out to replace the host tissue, are key steps for metastatic colonization. These obstacles make metastasis a highly inefficient process, but once metastases are established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
1,422
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,627 publications
(1,444 citation statements)
references
References 144 publications
(161 reference statements)
11
1,422
1
10
Order By: Relevance
“…The migration of cancer cells was a predominant element leading to cancer recurrence 20. Compared with the saline group, CLG, Taxol (free drug formulation), and naked let‐7a did not suppress cell migration (Figure 4C,D).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The migration of cancer cells was a predominant element leading to cancer recurrence 20. Compared with the saline group, CLG, Taxol (free drug formulation), and naked let‐7a did not suppress cell migration (Figure 4C,D).…”
Section: Resultsmentioning
confidence: 92%
“…The 4T1 tumor is a highly metastasis breast cancer, predominantly metastasizing to the lung and secondarily to the liver 20, 23. Accordingly, metastasis of 4T1 tumor to lung in 4T1 tumor‐bearing BALB/c mice was investigated at day 16 postadministration.…”
Section: Resultsmentioning
confidence: 99%
“…EMT is first observed during embryogenesis in the developing fetus, but is also present during wound healing, tumor progression and tumor invasion. [29][30][31][32][33] In thyroid tumors, EMT has been linked to papillary thyroid carcinoma (PTC) progression with overexpression of vimentin and has been associated with invasion and lymph node metastasis. 34 EMT has been associated with dedifferentiated cancers such as anaplastic thyroid carcinomas (ATCs) with decreased expression of E-cadherin and membranous β-catenin and increased expression of Slug and Twist1.…”
mentioning
confidence: 99%
“…34 EMT has been associated with dedifferentiated cancers such as anaplastic thyroid carcinomas (ATCs) with decreased expression of E-cadherin and membranous β-catenin and increased expression of Slug and Twist1. [29][30][31][32][33] Using a breast cancer model, Mani et al 23 showed that acquisition of mesenchymal traits was linked to the acquisition of stem cell markers. They further showed that transformed mammary epithelial cells that had undergone EMT formed spheres, soft agar colonies and formed in vivo tumors more efficiently suggesting that the EMT program that enabled cancer cells to spread from a primary tumor may also promote their self-renewal properties.…”
mentioning
confidence: 99%
“…Metastatic tumors often respond poorly to standard therapies, underscoring the need for new and effective drugs targeting metastasis [1]. Several factors are thought to determine the survival and growth of disseminated cancer cells in a distant microenvironment.…”
mentioning
confidence: 99%